2017
DOI: 10.1093/gji/ggx309
|View full text |Cite
|
Sign up to set email alerts
|

Improving the seismic small-scale modelling by comparison with numerical methods

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Note that the piezoelectric transducer response, including coupling effects can slightly modify the source waveform. These phenomena have been already pointed out by Bretaudeau et al (2011) and further studied by Pageot et al (2017) who demonstrated their reproducibility. They can be taken into account in numerical simulation by inverting the source wavelet as explained below.…”
Section: The Reduced-scale Measurement Bench Muscmentioning
confidence: 54%
See 1 more Smart Citation
“…Note that the piezoelectric transducer response, including coupling effects can slightly modify the source waveform. These phenomena have been already pointed out by Bretaudeau et al (2011) and further studied by Pageot et al (2017) who demonstrated their reproducibility. They can be taken into account in numerical simulation by inverting the source wavelet as explained below.…”
Section: The Reduced-scale Measurement Bench Muscmentioning
confidence: 54%
“…The scale ratio for the wavelength is 1000 implying that a distance of 10 m in reality is 10 mm in the laboratory. Note that compared to the ratio presented in Pageot et al (2017), we take into consideration a scale ratio equal to 2 for the seismic velocities. This allows us to simulate near surface media which have low seismic velocities by epoxy resins which have higher seismic velocity due to their stiffness.…”
Section: The Reduced-scale Measurement Bench Muscmentioning
confidence: 99%
“…This approach has shown a very good efficiency to assess physical properties of the considered sea dike, even for materials outside the vertical plan defined by the source-receivers line: the resulting model is virtually identical to the true one. An evaluation with more realistic data such as data from experimental small-scale modeling (Bretaudeau et al, 2011;Pageot et al, 2017) must be performed, but it seems at this stage that, even with field data, this method will be able to provide well defined image of the material distribution of a structure and an accurate reference model suitable for perturbation based imaging and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…But for more complex configurations, for instance, setups with strongly curved interfaces generating wave focusing/defocusing, or setups prone to multiple diffractions, a further investigation is necessary. Therefore, the framework must be adapted accordingly, preferentially by following a crossvalidation approach between numerical tools and the laboratory setup (Pageot et al, 2017, Solymosi et al, 2018. Indeed, the comparison between the experimental and numerical results usually emphasizes the improvements of the experimental setup that must be made to increase the accuracy (and decrease the uncertainties) of the experiments, and at the same time, it points out the limitations of the numerical tools that must be tackled.…”
Section: Introductionmentioning
confidence: 99%